1957
DOI: 10.1113/jphysiol.1957.sp005700
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and function of collateral sprouting in the sympathetic nervous system of the cat

Abstract: It is now established that surviving axons in incompletely denervated striated muscle extend their existing fields of innervation by a process of collateral sprouting, thereby accounting for the functional recovery which occurs (for review see Edds, 1953). A similar process also occurs in skin partly deprived of its sensory nerve supply (Weddell, Guttmann & Gutmann, 1941). Although the phenomenon has not been directly observed in the sympathetic nervous system, there is evidence of remarkable recovery of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

1960
1960
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(66 citation statements)
references
References 30 publications
3
63
0
Order By: Relevance
“…Since the cross-union operation resulted in the chromatolytic death of about two thirds of the spinal ganglion cells, their degenerating central terminals may have stimulated sprouting of adjacent Ia afferent fibres which then established the aberrant synaptic connexions on the Per motoneurones. This effect of degenerating nerve fibres was first demonstrated in partial muscle denervation (Hoffman, 1950(Hoffman, , 1951Edds, 1950Edds, , 1953, and it has also been found in the partially denervated sympathetic ganglion (Murray & Thompson, 1957) and in the spinal cord when spinal cord section caused degeneration of the descending tracts (McCouch, Austin, Liu & Liu, 1958).…”
Section: Discussionmentioning
confidence: 99%
“…Since the cross-union operation resulted in the chromatolytic death of about two thirds of the spinal ganglion cells, their degenerating central terminals may have stimulated sprouting of adjacent Ia afferent fibres which then established the aberrant synaptic connexions on the Per motoneurones. This effect of degenerating nerve fibres was first demonstrated in partial muscle denervation (Hoffman, 1950(Hoffman, , 1951Edds, 1950Edds, , 1953, and it has also been found in the partially denervated sympathetic ganglion (Murray & Thompson, 1957) and in the spinal cord when spinal cord section caused degeneration of the descending tracts (McCouch, Austin, Liu & Liu, 1958).…”
Section: Discussionmentioning
confidence: 99%
“…The responses that remain were due to preganglionic axons running in the an~za8ubclavia. of selected spinal cord segments (Murray & Thompson, 1957;Guth & Bailey, 1961;Guth & Bernstein, 1961).…”
Section: Resultsmentioning
confidence: 99%
“…However, if the ganglion is partially denervated by interrupting the sympathetic rami T1-T3, the residual preganglionic axons, arising from T4-T7, will sprout and establish new synaptic connexions with ganglion cells that are obviously inappropriate to them. Thus several weeks after partial denervation, stimulation of the residual preganglionic axons elicits an abnormally wide range of peripheral sympathetic effects, including dilatation of the pupil, a response which is normally elicited only by preganglionic axons arising from T1-T3 (Murray & Thompson, 1957;Guth & Bailey, 1961;Guth & Bernstein, 1961). This loss ofspecificity might be a consequence ofthe complete removal ofpreganglionic axons arising from particular spinal levels.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence accumulated from experimental work has shown that, following a partial lesion in the nervous system, terminals with injured fibers degenerate and intact afferent fibers progressively sprout collaterally to occupy the evacuated regions. [18][19][20][21][22] Reorganization of the nervous system comprises degenerative and regenerative changes in the afferent neurons distal to the lesion sites, disorganization and reorganization of the whole network, and ultimately the new growth. [22][23][24][25][26][27][28][29] It is suggested that the process of degeneration, reorganization and sprouting results in an alteration of the 'synaptic zone', which is the very element of the nervous system transmitting information from one neuron to another, forming the basis of the reflex behavior.…”
Section: Mechanisms Underlying Rf Of Antagonist Muscles In Scimentioning
confidence: 99%